2022
DOI: 10.1021/acsanm.2c02689
|View full text |Cite
|
Sign up to set email alerts
|

Nanoporous AlGaN Distributed Bragg Reflectors for Deep Ultraviolet Emission

Abstract: In this paper, we demonstrated wafer-scale AlGaN-based deep ultraviolet (DUV) nanoporous (NP) distributed Bragg reflectors (DBRs) by vertical electrochemical (EC) etching. The stopbands of the NP-DBRs were centered around 280 nm with reflectance close to 90%. A thick AlGaN film and four-period multiple quantum wells (MQWs) were grown on the strain-relaxed NP-DBRs template. The reciprocal space mappings (RSMs) revealed the increased compressive strain in MQWs grown on NP-DBRs, and transverse electric (TE) mode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Due to the improvement in LEE, compared to the AlGaN-based DUV-LEDs with Ni/Au as a p-type electrode, the wavelength of 278 nm, the wall insertion efficiency of AlGaN-based DUV-LEDs is improved by 57%. In addition to the study of highly reflective electrode structures, other reflective structures such as photonic crystals [96], Distributed Bragg Reflectors(DBRs) [97], and omnidirectional reflectors [98] have been investigated for the improvement of LEE. The LEE of LEDs is also improved by the increase of the sidewall emission, so the study of the sidewalls of AlGaNbased DUV-LEDs is also another idea to enhance the LEE of the TM mode [108].…”
Section: Structural Design Of Highlight Extractionmentioning
confidence: 99%
“…Due to the improvement in LEE, compared to the AlGaN-based DUV-LEDs with Ni/Au as a p-type electrode, the wavelength of 278 nm, the wall insertion efficiency of AlGaN-based DUV-LEDs is improved by 57%. In addition to the study of highly reflective electrode structures, other reflective structures such as photonic crystals [96], Distributed Bragg Reflectors(DBRs) [97], and omnidirectional reflectors [98] have been investigated for the improvement of LEE. The LEE of LEDs is also improved by the increase of the sidewall emission, so the study of the sidewalls of AlGaNbased DUV-LEDs is also another idea to enhance the LEE of the TM mode [108].…”
Section: Structural Design Of Highlight Extractionmentioning
confidence: 99%
“…14, x FOR PEER REVIEW 12 of 18 without a FSODR, the LEE of DUV LEDs with a FSODR increased by 60%. Recently, Shan et al researched wafer-scale AlGaN-based deep ultraviolet (DUV) nanoporous (NP) distributed Bragg reflectors (DBRs), as shown in Figure8; the experimental results showed that due to the reflection effect caused by the NP-DBRs, the light extraction of both the TE and TM modes improved[107].…”
mentioning
confidence: 99%
“…There are also methods of isolating IC elements using etched grooves on the surface of the substrates. In particular, insulation using V-grooves, filled polycrystalline silicon (VIP-method, VIP-V-brave isolation polisilicon) is based on vertical anisotropic etching of silicon substrates with formation of V-shaped grooves filled with polycrystalline silicon [9,10]. V-ATE -technology (V-ATE -vertical anisotropic etch) is available a variant of the method of combined isolation of components, in which the separation tracks are not filled with silicon dioxide or others insulating materials [10,11].…”
mentioning
confidence: 99%